SOLITON SOLUTIONS FOR BOGOYAVLENSKY-KONOPLECHENKO AND JAULENT-MIODEK EQUATIONS VIA EXTENDED (G?/G)-EXPANSION METHOD - İnç, Mustafa; Kilic, B.; Ugurlu, Y. (Editura Acad Romane, 2015)
In this paper, we apply the extended (G'/G)-expansion method to construct exact solitary wave solutions, topological solitons, and singular solitons of Bogoyavlensky-Konoplechenko (BK) and Jaulent-Miodek (JM) nonlinear evolution equations.
Keywords: Bogoyavlensky-Konoplechenko equation; Jaulent-Miodek equation; Extended (G '/G)-expansion method; soliton